A Fatigue Equivalent Static Load Methodology for the Fatigue Life Estimation of Load Haul Dumpers (The Australasian Institute of Mining and Metallurgy, 2005)
A methodology for the fatigue life estimation of load haul dumpers, employed in underground platinum mines, has been developed and applied. This method entails the quantification of operating conditions by means of stress measurements. The measurements are then translated into a fatigue loading factor for a finite element model. The results of this analysis are then used to compare all the critical connections in the structure to detail categories in relevant fatigue codes, and predict a life in operating hours for the vehicle structure. The method was applied on a specific model and the results of this analysis were compared to actual failure occurrences with reasonable accuracy. It is intended that the methodology be embedded into performance specifications and purchasing contracts and that technology transfer to OEMs be achieved. Based on the experience of this project and other similar exercises it is estimated that structural life expectancies may be increased across a typical fleet of trackless mining vehicles (LHDs, drill rigs, utility vehicles, dump trucks) by at least 20 per cent.